PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM MENGELOLA TRANSAKSI KEUANGAN PADA BUMDES USAHA BERSAMA KABUPATEN SINTANG - Steven Dharmawan, Weiskhy; Yulia, Yulia; desiyana, fransiska (Jurnal Sistem Informasi Akuntansi, 2023)
Technology and information are currently experiencing developments, automatically demanding that all areas of activity be computerized, one of which is in the field of accounting. BumDes Joint Enterprises of Gemba Raya Village, Kelam Permai District, Sintang Regency is a village-owned business institution engaged in the sale of agricultural products, namely the sale of fertilizers and grass poison. The problem faced by BumDes Joint Ventures is the processing of financial data which is still manual using bookkeeping records including in the preparation of financial reports such as collecting transaction evidence processing data, recording general journals, recording general ledgers, recording balances, recording adjusting journals, recording work balances and ending with financial reports (balance sheets, profit/loss reports, and reports on changes in capital). For this reason, the authors recorded financial transactions using Zahir Accounting software version 6.0 on the BumDes Joint Ventures of Sintang Regency. Using Zahir Accounting version 6.0 can provide a solution for BumDes Usaha Bersama in making financial reports more effective and efficient so that they can support financial transaction activities at this institution.